LAW ENFORCEMENT OF CORPORATE CRIME IN FOREST FIRE IN INDONESIA - Lasmin Alfies Sihombing (Sean Institute, 2022)
Corporate crime is an organizational crime. One of the forms of corporate crime that is of concern because of the ever-increasing developments is the form of corporate crime in the environmental sector, one of which is forest fires. Corporate crimes in the environmental field can cause large and complex impacts and victims that not only deplete natural resources, human resources, social capital, even sustainable institutional capital. This study aims to determine corporate criminal responsibility in forest fires in Indonesia, and law enforcement against corporate criminal acts in forest fires in Indonesia. This study uses a descriptive analysis method with a normative juridical approach. Corporate criminal responsibility for burning forests and land in Indonesia, can use forestry and environmental laws as a legal basis for imposing criminal liability on corporations. As for the perpetrators of forest burning by the activities of companies engaged in plantations or human carelessness, this can be charged with Article 50 of Law Number 41 of 1999 in conjunction with Law Number 19 of 2004 concerning Forestry, also violating Article 11 of Government Regulation Number 4 of 2001 as well as Article 187 and Article 188 of the Criminal Code. Law Enforcement of Corporate Criminal Acts of Forest Burning in connection with Law Number 32 of 2009 concerning Environmental Protection and Management, law enforcement in the environmental field can be classified into 3 (three) categories, namely Environmental law enforcement in relation to State Administrative / Administrative Law, Environmental Law Enforcement in relation to Civil Law; Environmental Law Enforcement in relation to Criminal Law.